B-Type Natriuretic Peptide (BNP) Detection Using Electrochemical Immunosensor Based on Sandwich ELISA with Horseradish Peroxidase-Tetramethylbenzidine System. (2017) - Hartati, Yeni Wahyuni; Nurmalasari, Ratna; Gaffar, Shabarni; Subroto, Toto
Abstract: A study of B-type natriuretic peptide (BNP) antigen as a good prognostic marker for patients with heart failure antigen detection employing an electrochemical immunosensor is described here. Monoclonal anti-BNP capture antibody was immobilized on streptavidin-modified SPCEs to increase the sensitivity of the assay. An anti-BNP detection antibody conjugated with horseradish peroxidase enzyme (HRP) and 3, 3, 5, 5'-tetramethybezidine dihydrochloride (TMB) was used as a substrate, in connection with voltammetric technique was achieve by measuring the peak current. Incorporation of a streptavidin/biotin system resulted in a well-oriented antibody immobilization of the capture antibody and consequently enhanced the sensitivity of the assay. Several optimizations were performed to reduce background signals; the optimal concentration of anti-BNP detection antibody needed, the time of SPCEs were first blocked with glycine, incubated with various concentrations of BNP and HRP-conjugated anti-BNP detection antibody (0 to 100.0 ng/mL), followed by electrochemical measurement were investigated, . In conclusion, this immunosensor greatly shortened and convenient for detection of heart failure diagnosis in real serum samples.